(untitled) (Historia, 2021)
An interesting phenomenon found in earlier centuries in the Netherlands and areas within her sway of influence was the custom of producing commemorative medals (familiepenningen) to record family events, from the cradle to the grave. Most extant medals relate to weddings and wedding anniversaries although a fairly large number were made as gifts for family and friends who participated in the last rites of a loved one. The practice seems to have been typically Dutch, with a more limited usage in the protestant cities of Northern Germany. A study of these medals is of importance far beyond the closed circle of medal collectors. Art historians, iconographers, genealogists and heralds can all benefit from such investigation.